Influence of UV-radiation on structure and properties of diamond-like a-C:N films - Shalaev, R.V.; Varyukhin, V.N.; Prudnikov, A.M. (Functional Materials, 2004)
Study results on effect of a low power (up to 1 W/cm²) UV and visible radiation on the structure and properties of diamond-like carbon nitride (α-C:N) films during their growth have been presented. The UV irradiation of the growing film surface has been found to be effective for the graphite phase etching and to result in an improved structure ordering of the film and enhanced quality thereof. Представлены результаты исследования воздействия УФ- и видимого излучения невысокой мощности (до 1 Вт/см² на структуру и свойства алмазоподобных пленок нитрида углерода α-C:N в процессе их роста. Обнаружено, что УФ-облучение ростовой поверхности пленок эффективно для травления графитной фазы, ведет к росту структурной упорядоченности пленок и улучшает их качество. Представлено результати досліджєння впливу УФ- i видимого випромінювання невисокої потужності (до 1 Вт/см²) на структуру і властивості алмазоподібних плівок нітриду вуглецю α-C:N у процесі їхнього росту. Виявлено, що УФ-опромінення ростової поверхні плівок ефективно для травлення графітної фази, веде до росту структурної упорядкованості плівок і поліпшує їхню якість.